The use of video as a tool for reflection with preservice teachers. Issue 4 (2nd October 2018) - Xiao, Bing; Tobin, Joseph
ABSTRACT: This study explores how the process of making and reviewing videos of their own instruction impacts the development of preservice teachers. The study looks at the impacts, both positive and negative, of a video portfolio assignment implemented in a teaching methods course, and of the uses and meanings these videos have for preservice teachers, their instructors, and the teacher preparation program. Findings suggest that the videotaping assignment has the virtue of shifting attention to the often-overlooked embodied dimensions of teaching (e.g., gesture, posture, gaze, tone of voice, facial expressions, use of materials, and positioning). On the other hand, the requirement to videotape themselves teaching can produce anxiety that can make preservice teachers tend towards self-conscious, teacher-centered versions of teaching. The article concludes with implications for how initial teacher preparation programs can implement the videotaping requirement of edTPA in ways that best support preservice teachers' growth.